2009
DOI: 10.1177/0269881109106957
|View full text |Cite
|
Sign up to set email alerts
|

Clinician experiences of employing the AmpliChip® CYP450 test in routine psychiatric practice

Abstract: These findings are from a qualitative study examining clinician experiences of employing the AmpliChip® CYP450 test in psychiatric practice. One hundred tests were made available to secondary care mental health service clinicians commencing patient treatment with risperidone across three District Health Boards within New Zealand. Feedback was sought on clinicians' (n = 33) experiences of ordering the test and receiving results, utilization of results, and perceived advantages and disadvantages. Difficulties we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(74 citation statements)
references
References 8 publications
1
68
0
5
Order By: Relevance
“…Various polymorphisms in these enzymes predispose an individual to enhanced or poorer therapeutic and/or side-effect response to certain medications. Despite robust findings of association with the particular CYP450 genotypes and altered response to psychotropics, there remains insufficient evidence to support CYP450 genotype screening [236,381]. Additionally, many of the genetic alterations described in this review also are relevant to pharmacogenomic paradigms.…”
Section: Resultsmentioning
confidence: 97%
“…Various polymorphisms in these enzymes predispose an individual to enhanced or poorer therapeutic and/or side-effect response to certain medications. Despite robust findings of association with the particular CYP450 genotypes and altered response to psychotropics, there remains insufficient evidence to support CYP450 genotype screening [236,381]. Additionally, many of the genetic alterations described in this review also are relevant to pharmacogenomic paradigms.…”
Section: Resultsmentioning
confidence: 97%
“…In a study by Dunbar et al, sponsored by Roche Molecular Diagnostics, the authors report that upon surveying 33 clinicians who were using the Amplichip † test there were some logistic difficulties with the test (i.e. ordering and receiving results) however, the clinicians widely reported advantages to the test, such as support of their dosing decisions (147). The reported disadvantages varied from over-reliance on the test to the actual implementation of a new clinical procedure, breaking away from routine practice.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…The reported disadvantages varied from over-reliance on the test to the actual implementation of a new clinical procedure, breaking away from routine practice. Their findings indicate that overall, psychiatric clinicians are open to pharmacogenetic testing in clinical practice if its implementation is done with economic consideration (147). On the patient side, Swen et al performed a study using the Amplichip † to investigate the feasibility of pharmacy-initiated pharmacogenetic testing of CYP metabolizer status by inviting 93 patients to participate in the testing.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…The reviewers concluded that "psychiatric clinicians are receptive to employing this test as a clinical support tool if its implementation is carefully considered and economically justifiable" (Dunbar 2009). For instance, a 2009 review of the test in psychiatric practice determined that the AmpliChip CYP450 played a "supporting role with regard to dosing decisions, rather than being the main influence on clinician behavior" and said that the test was viewed as "potentially useful in facilitating the development of the doctor-patient relationship."…”
Section: Roche's Amplichip Cyp450mentioning
confidence: 99%